Kentuckian’s Attitudes on Capital Punishment, 1989–2016 - Vito, Gennaro F. (American journal of criminal justice, 2018)
Citizens’ attitudes toward the death penalty have been effected by the availability of life without parole (LWOP). Our analysis focuses upon data from a representative sample of Kentuckians on death penalty attitudes. The factors influencing and related to death penalty support and compared to support for LWOP are considered along with a review of Kentucky survey findings from 1989–2016. The results reveal consistent support for LWOP over the death penalty. Male Kentucky residents with a college education were most likely to support life without parole over capital punishment while male conservatives did not.